Heart-specific expression of the green fluorescent protein gene in avian embryos by administration of recombinant adenovirus type-5 vector into the embryonic blood vessel - Choi, Wonjun; Lee, Joonbum; Kim, Dong-Hwan; Ma, Evan; Suh, Yeunsu; Lee, Sang-Suk; Lee, Kichoon (Frontiers in Physiology, 2024)
Genetic modification in vivo could provide direct functions of genes that could potentially contribute to diverse areas of research including genetics, developmental biology, and physiology. It has been reported that genes of interest could be introduced via recombinant adenovirus type 5 (Ad5) in poultry. Successful gene delivery to mammal fetuses in utero promises substantial progress in clinical and developmental biology, but it is limited because of difficulties in injecting specific sites and invasiveness. On the other hand, developing avian embryos are easily accessible by making a window on the eggshell. Therefore, the objective of this study is to determine permissive embryonic stages for gene transfer into specific avian tissue/organs by injection of Ad5 containing the green fluorescent protein (GFP) gene into blood vessels. At 2 d of post-injection, a strong GFP signal was predominantly identified in the heart of chicken embryos injected at Hamilton-Hamburger (HH) 14, 15, 16 and17 stages with the percentages (44%, 53%, 25%, and 14%, respectively) of GFP positive embryos. In quail embryos, the injection at the HH 15 resulted in heart-specific expression of GFP. Western blot analysis revealed that GFP was exclusively expressed in the avian hearts. These results suggest that the GFP gene is specifically delivered to the avian embryonic hearts when Ad5 is injected through the blood vessel at HH 14-17. This adenoviral transduction of genes of interest in avian embryonic hearts can provide new models for understanding functions of genetic factors on embryonic heart development and unravel genetic etiology of congenital heart diseases.